Reviewing the environmental implications of increased consumption and trade of biofuels for transportation in Sweden. Issue 2 (17th February 2020) - Martin, Michael; Larsson, Mathias; Oliveira, Felipe; Rydberg, Tomas
ABSTRACT: Sweden, a European leader in the consumption of biofuels, has surpassed targets set by the EU and is one of a few countries that has increased consumption of biofuels in recent years. Nonetheless, a large share of biofuels, and raw materials used to produce the fuels, are imported from regions outside Sweden. This paper reviews the environmental implications of consumption of biofuels in Sweden 2000–2014 to identify and provide a comprehensive assessment of the environmental impacts that imports of fuels have both in Sweden and abroad using life cycle assessment (LCA). The results suggest that while greenhouse gas emissions may have been reduced in Sweden by the use of biofuels, the origin of the emissions has shifted from Sweden to Europe and other countries abroad, due in part to an increased use of biofuels and raw materials from abroad. This has important implications for local impacts, as this may increase acidification and eutrophication potential and ecotoxicity created abroad. Thus, although policy has been designed to promote sustainable transportation fuels, in addition to the generation goals set by the Swedish Parliament, the implications on regions exporting fuels and raw materials for Swedish consumption should be reviewed and followed in further detail in order to avoid problem shifting.